The Effect of the Implementation of Local Government Information Systems (SIPD) and Human Resources on Regional Financial Management Accountability - Nurmila Daud; Harun Blongkod; Nilawaty Yusuf (Mandalika Journal of Business and Management Studies, 2025)
This study aims to analyze the influence of the implementation of the Local Government Information System (SIPD) and the quality of Human Resources (HR) on the accountability of regional financial management in Regional Apparatus Organizations (OPD) in Gorontalo Province. SIPD functions as an information system that supports transparency, efficiency, and accuracy in regional financial management, while the quality of human resources plays a role in ensuring that the implementation of the system can run optimally. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method to test the relationship between variables. The research sample consisted of 142 civil servants who served in the Gorontalo Province OPD and were involved in regional financial management. The results of the study show that SIPD has a positive and significant effect on the accountability of regional financial management, especially in the aspects of efficiency, transparency, and accuracy of financial data. In addition, HR also has a significant influence on accountability, where employees who have an understanding of financial regulations and the ability to operate SIPD tend to be more responsible in reporting and managing regional budgets. Simultaneously, SIPD and HR have a very strong influence on regional financial accountability, with a contribution of up to 100% in explaining the variation in financial accountability. However, there are several obstacles in the implementation of SIPD, such as lack of employee training and technical obstacles in the system. Therefore, local governments need to increase continuous training for ASN and conduct periodic evaluations of the effectiveness of SIPD to ensure better transparency and accountability in regional financial management.